Experimental Study on Axial Compression of Bamboo Scrimber Cold-Formed Thin-Walled Steel Composite Special-Shaped Columns - Chao Lei; Yuhao Wu; Bingyang Yang; Bingbing Wang; Jianqiang Han; Xiuyan Fu (Buildings)
As one of the four key sectors for energy saving and emissions reduction, the construction industry faces ongoing high energy consumption and emissions. To support China’s sustainable development, urgent promotion of green construction and energy-saving measures is necessary. This led to the proposal of nine specimens of L-shaped, T-shaped, and cross-shaped engineered bamboo, cold-formed thin-walled steel, and their combinations for axial compression tests to study the effect of bamboo–steel structures on axial compression performance. The results showed that the load-bearing capacity of the three bamboo–steel composite columns increased by 19.5–21.4% compared to the sum of steel composite and L-shaped bamboo composite columns, significantly enhancing overall stability and deformation capacity. The synergy between steel and engineered bamboo effectively addressed the instability issues of steel structures with large width-to-thickness ratios. Using Abaqus finite element software for simulation, the stress distribution at failure and load-displacement curves were closely aligned with experimental outcomes. The study presents a formula for calculating the axial compression capacity of cold-formed thin-walled steel-engineered bamboo composite columns, with theoretical and experimental discrepancies within 13.28%, offering a theoretical basis for the design of engineered bamboo–steel composite columns.